(untitled) - Bailey, Alton Edward (Hoboken, N.J., 2005)
The additional volume is mainly on specialty oils and fats and their by products or minor components as well as on those of low-calorie fat substitutes and structured lipids. An article on fish oils one on marine mamal oils are also included in this volume.
Keywords: Oils and fats.,Công nghệ dầu ăn